In silico elucidation of protein-protein interaction network in fish pathogen Flavobacterium Columnare - Nematiasgarabad, Pershia; Hashim, Nikman Adli Nor; Yahya, Mohd Fakharul Zaman Raja (Malaysian Applied Biology, 2024)
Flavobacterium columnare is a virulent intracellular bacterial pathogen that causes an infection known as columnaris in many species of fish. Some economically important fish species are strongly affected by columnaris, leading to a high mortality rate and significant economic losses. Previous in silico studies have provided various biological insights into F. columnare, including its interaction with MHC class I alleles and the epitopic region within outer membrane proteins. However, the protein-protein interaction networks underlying the growth, defense, and pathogenesis of F. columnare remain largely unknown. This study was conducted to identify the protein-protein interaction (PPI) networks and hub proteins of F. columnare that can be used as drug or vaccine targets. A total of 500 protein sequences were retrieved from UniprotKB in FASTA format and analyzed using VaxiJen, PSORTb, STRING, Cytoscape, and BLASTp programs. The results demonstrated that 60% of F. columnare proteins were predicted as antigenic proteins, most of which were associated with catalytic activity and metabolic processes, identified as cytoplasmic proteins. Ten hub proteins with the highest number of functional interactions were identified, which were also antigenic and non-host homologous. In conclusion, F. columnare hub proteins represent potential therapeutic targets in drug and vaccine development against columnaris infection.